Cardiometabolic Dysregulation and Heart Failure - Susannah Ashfield; Utkarsh Ojha (Reviews in Cardiovascular Medicine)
Heart failure (HF) is a complex clinical syndrome resulting from impaired myocardial function or structure, affecting approximately 56 million patients worldwide. Cardiometabolic risk factors, including hypertension, insulin resistance, obesity, and dyslipidemia play a pivotal role in both the pathogenesis and progression of HF. These risk factors frequently coexist as part of cardiometabolic syndrome and contribute to widespread organ and vascular dysfunction, leading to conditions such as coronary artery disease, chronic kidney disease, type 2 diabetes mellitus, non-alcoholic fatty liver disease, and stroke. Emerging evidence suggests that these conditions not only increase the risk of developing HF, but also negatively impact its progression and outcome. As the global burden of cardiometabolic disease continues to rise, a growing number of HF patients will exhibit multiple metabolic comorbidities. Understanding the intricate relationship between cardiometabolic risk factors and diseases and their impact on HF outcomes is therefore crucial for identifying novel therapeutic avenues. A more integrated approach to HF prevention and management—one that considers these interconnected cardiometabolic factors—offers significant potential for improving patient outcomes.